(3GdJhLjg TQM GdeZfj eNJUQ GdJfHjgs - (3HQgGf GdOjf EHQGgje Hf ehSi GdEjfGSs; (3CHh GdbGSe,J (B738 (3g` s
(3ChdgG (B:s
(3jHOC HcJGH GdLfGjGJ s
(3BNQgG (B:s
(3bGd Gabjg hdG hLg dg dCf GdHZhj UhQgG HeG EPG cGf GdJaSjQ efaUdkG hGddg JYGdi CYde s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs